First Report of Alternaria alternata Causing Leaf Spot on Orange (Citrus sinensis (L.) Osbeck) in Karbala Province, Iraq - L. Hameed , Zainab (Pure Sciences International Journal of Kerbala, 2026)
During a field survey conducted in 2022 in citrus groves in Alhusaynia territory, Karbala Province, Iraq, leaf spot symptoms were observed on orange foliage. A fungal pathogen was regularly isolated from diseased leaves and identified as Alternaria alternata based on colony and conidial morphology and internal transcribed spacer (ITS-rDNA; PX763615.1) sequence analysis. Pathogenicity was evaluated using a detached-leaf assay, and typical symptoms were reproduced on inoculated leaves, followed by re-isolation of the same fungus. This investigation is the first documented occurrence of A. alternata associated with leaf spot on orange in Karbala Province, Iraq